Occupational Safety Aspect of Work Implementation Improved Road Capacity - Bambang Istiyanto; Raudatul Jannah (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2020)
Along with the increase of vehicle ownership, progress in the field of industry and commerce, and the distribution of goods and services led to increased traffic volume. Jambi City Government through the Department of Public Works and Spatial Planning has a special program to improve the quality of roads in several locations in Jambi City to realize “Jambi Bangkit 2018”. One is a project to increase the capacity of Sunan Giri Street. Road status of the city is an alternative way that every day is always crowded with vehicles, especially peak hour in the morning and afternoon. Therefore, a much needed additional capacity on the road section with the hope to meet the elements of smoothness, comfort, security and safety of road users. However, based on results of the review in the field, still found some problems related to road safety. Recommendations are given is that with the addition of temporary traffic sign, hazard management, procurement officer traffic controller at a busy time (Peak Hour) and to equip workers PPE project to improve safety during construction.